Kondisi Terumbu Karang di Perairan Pulau Tegal dan Sidodadi Kecamatan Padang Cermin Kabupaten Pesawaran Provinsi Lampung - Hartoni .; Ario Damar; Yusli Wardiatno (UNIVERSITAS SRIWIJAYA, 2012)
Coral reefs are ecosystem that have important economic value, but very fragile towards natural factor and human activities. Increasing human activities around the coastal waters will affect the ecosystem of coral reefs. The research was conducted from April to July 2010. The purpose of this study were to analyze the current state of coral reefs, to analyze the extent of damage and identify the cause of damage in Tegal island and Sidodadi waters. Percentage of life coral cover was obtained using line intercept transect (LIT) method. The results showed that percentage of life coral cover at 6 observation stations approximately 37.76% - 65.90%. The highest percentage live coral cover at Station 2 and the lowest at Station 3. In general, the condition of coral reef life was categorized